Microstructural evolution and mechanical properties of non-Cantor AlCuSiZnFe lightweight high entropy alloy processed by advanced powder metallurgy - Sharma, Ashutosh; Oh, Min Chul; Ahn, Byungmin (Materials Science and Engineering: A, 2020)
In this study, multicomponent AlCuSiZnFe high entropy alloy (HEA) was fabricated through high energy ball milling (HEBM) of constituent powders, and further densification via spark plasma sintering (SPS). The results show the presence of a predominant face-centered cubic (FCC) phase with a minor body-centered cubic (BCC) phase in (45 h) HEBMed powders which further develop according to the SPS treatment. At a low SPS temperature of 600 °C, the alloying of individual elements was poor. Further, at 650 °C, alloying improves and the liquid Cu–Zn FCC phase separates from the high-temperature Fe–Si-rich BCC phase during SPS. At 700 °C, Al was noticed to stabilize the BCC phase leaving behind soft FCC (Cu–Zn). Further increase in SPS temperature to 800 °C causes a complete melting of HEA compacts and the formation of Cu–Al intermetallic compounds (IMCs). The microhardness of the HEA compacts increases with SPS temperature in the range of 690–974 HV. The compressive properties were found to be optimum at 650 °C, compressive strength ≈1987 MPa and elastic modulus ≈27,945 MPa respectively. The measured densities of HEAs varied from 4.98 to 5.24 g/cm3, comparable to the heaviest of lightweight Ti alloys reported so far.
Keywords: Body-centered-cubic phase; Densifications; Face-centered cubic phasis; High entropy alloys; High-energy ball milling; Light weight alloys; Minor bodies; Multicomponents; Sintering temperatures; Spark-plasma-sintering; High entropy alloys; Lightweight alloys; Microstructure; Powder metallurgy; Spark plasma sintering